Corporate Social Responsability for the Competitiveness of the Organizations in Mexico - Lara Manjarrez, Itzel Alejandra; Sánchez Gutiérrez, José (Mercados y Negocios, 2020)
Corporate social responsibility is determined as one of the most useful strategies within organizations for the achievement of competitive advantages. The present work is based on the existing literature of different business visions and how these can be adapted to achieve social benefits within the organization. As a result, it was obtained that social responsibility in Mexico is an element that generates long term benefits for the orgainzation, including increased competitiveness due to higher profitability, better brand image and better internal relashionship of the company.